Health literacy of Samoan mothers and their experiences with health professionals - Vili Nosa; Fofoa H. Pio (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONPatient and health professional engagement is a crucial factor for the effectiveness of service delivery and the management of care. Low health literacy amongst Pacific peoples is likely to affect their engagement with health professionals. AIMTo explore the health literacy of Samoan mothers and their experiences with health professionals in primary care. METHODSTwenty Samoan mothers and caregivers living in Auckland were interviewed about their experiences when engaging with health professionals. Semi-structured interviews guided by open-ended questions were conducted with individual participants in either Samoan or English. The interviews were recorded, transcribed and analysed. RESULTSA key finding was the significance of the health professionals' role, in particular general practitioners, in providing resources and information to participants. Many participants recognised their general practitioner as their primary source of information. The findings revealed the negative experiences participants faced while engaging with general practitioners and shared how this affected their ability to manage care. Themes about enablers of open communication with health professionals included mothers understanding their rights as patients and being acknowledged as an expert on their child's health. Themes about barriers to open communication with health professionals included limited consultation time, language barriers, medical jargon, closed answers, power relations and the shame associated with not fully understanding. DISCUSSIONThis research can inform health care engagement practices with patients. This study is relevant to health-care providers, development of health resources, health researchers evaluating health-care communications between providers and patients, to inform culturally appropriate and effective health-care delivery. The importance of shared responsibility in addressing issues of health literacy is noted, shifting the focus to everyone involved in providing and receiving information and in making decisions and managing care.